Changes in the diagnosis and non-invasive treatment of chronic coronary syndromes in the last three European Society of Cardiology guidelines - Kozłowska, Izabela; Trzeciak, Przemysław; Gąsior, Mariusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2021)
One of the most common forms of ischemic heart disease is chronic coronary syndromes (CCS), formerly known as stable coronary artery disease. During the last 15 years, the European Society of Cardiology has modified the guidelines for the diagnosis and treatment of CCS three times. The aim of this study was to analyze the changes in non-invasive diagnostics and pharmacotherapy of CCS that occurred in the last three guidelines. In non-invasive diagnostics, the most important change was reduction of the role of the electrocardiographic exercise test in favor of non-invasive stress imaging tests and computed tomography angiography. In pharmacotherapy, the role of b-blockers and calcium channel blockers has increased in controlling heart rate and symptoms. Intensive hypolipemic treatment for prevention of cardiovascular events and treatment with low doses of novel oral anticoagulants for those at high risk of cardiovascular events with sinus rhythm are among the recommendations.